Pemenuhan Hak Anak Pada Keluarga Long Distance Relationship Perspektif Fiqih Hadhanah: (Studi Kasus di Desa Gedangan Kec. Maduran Kab. Lamongan) - Al Farisi, Salman; Taufiq Hidayat, Fiqanda (Muhammadiyah University of Surabaya, 2023)
The phenomenon of the Long Distance Relationship (LDR) family has become a social reality that is increasingly found in various regions, including in Gedangan Village, Maduran District, Lamongan Regency. This condition poses its own challenges in fulfilling children's rights, both physically, emotionally, and spiritually. From the perspective of children's fiqh, parents have a greatresponsibility in fulfilling their children's basic rights, such as the rights of nurturing, education, protection, and affection. This study aims to analyze how the fulfillment of children's rights in LDR families is reviewed from the perspective of fiqh hadhanah, as well as the factors that affect it. This research uses a qualitative approach with a case study type. Data collection techniques are carried outthrough observation, in-depth interviews with LDR families and community leaders, and documentation. The data obtained were analyzed descriptive-qualitatively with normative and sociological approaches. The results of the study show that in LDR families in Gedangan Village, most of them still fulfill the rights of their children, namely by sending their children to school to get their educational rights, meeting all needs, seeking health, providing protection to their children, giving the right to worship to theirchildren, and maintaining communication between family members. Although fathers are nomadic and physically absent from their children's daily lives, children's rights in terms of nurturing, education, health, and spiritual formation remain fulfilled through the mother's dominant role as a gift as well as the father's financial involvement and long-distance communication. This parenting pattern is in accordance with the principle of hadhanah in fiqh, which prioritizes the protection and benefit of children, and reflects the implementation of family responsibility in caring for offspring (hifzh al-nasl) even in geographically not ideal family conditions such as LDR. This study recommends the need for collaborative parenting strategies and the use of technology to bridge emotional distance in LDR families. Keywords: Children's Rights, LDR Family, Hadhanah Fiqh, Parenting.